(untitled) (Research, Society and Development, 2019)
This article is a cut of the master’s dissertation of the post-graduate program in Teaching Humanity and Languages - UFN. Therefore, the interest of this research starts from the need to (re) think about gender relations from the teacher training. In bringing these questions we intend to understand the discourse that normalized, naturalized and determined the place of men and women in the educational space. This allows us to review relationships as a human being and subject. In this sense, the research aims to present the narratives of teachers from the 1950s to 1970s from the discourse of etiquette and civility, showing the possible influence on teacher training. The methodology is characterized by being of a qualitative nature based on documental references and narrative analyzes. "The voice of the teachers". For data collection a questionnaire was applied and the technique used consisted of the hermeneutic method that allowed to relate the narratives with the social and historical contextualization interweaving with the manuals of etiquette and civility. As a result it was found that the etiquette and civility manuals printed signs considered indispensable to the feminine nature. Faced with this, the Faculty of Philosophy, Sciences and Letters (FIC), from 1953 to 1979, had a predominance of female classes, and, in this way, the importance and necessity of numerous copies of textbooks in the Faculty’s library was observed. It is concluded that the manuals influenced the choice and the way of acting of the teachers, normalizing the relations of power and gender in the space of teacher training.